Linking Evidence-Based Program Participant Data with Medicare Data: The Consenting Process and Correlates of Retrospective Participant Consents - Ritter, Philip Lloyd; Ory, Marcia G.; Smith, Matthew Lee; Jiang, Luohua; Alonis, Audrey; Laurent, Diana D.; Lorig, Kate (Frontiers in Public Health, 2015)
.